ANALYSIS OF REPRESENTATIVE ILLOCUTIONARY ACTS IN DOCUMENTARY MOVIE ON THE MINIMALISTS : LESS IS NOW - Widha Istika Winekas Hartono; Dias Andris Susanto; Faiza Hawa (Bajang Institute, 2022)
This study aims to determine the types and describe the most dominant and least appearance of representative illocutionary acts in the documentary movie entitled